MALE GAZE DALAM SASTRA FEMINIS: STUDI ATAS KARYA ABIDAH EL KHALIEQY DAN RATIH KUMALA - Febrianto, Anggit; Udasmoro, Wening (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2023)
Since the fall of Suharto in May 1998, women's involvement in literature has increased rapidly, causing a rush of feminist themes and content in literary works in this period. However, the literary works of women writers, even female feminists, are still unable to escape the tendency to objectify women. This study will show how women are positioned as objects of the voyeuristic scopophilia and fetishistic scopophilia of men in the Abidah El Khalieqy’s Perempuan Berkalung Sorban and Geni Jora and Ratih Kumala’s Tabula Rasa and Gadis Kretek. This study is descriptive qualitative. Data collection techniques were carried out using the literature study method, namely by reading carefully and thoroughly the four material object novels. Collected data will be analyzed using Male Gaze Theory by Laura Mulvey. The results of this study show that in the four novels, women consistently manifest as objects of the voyeuristic scopophilia and fetishistic scopophilia of men. This finding can be seen in the voyeuristic relationship between Samsudin-Annisa in Perempuan Berkalung Sorban, Zakky-Lola in Geni Jora, Idroes-Roemaisa in Gadis Kretek; as well as in the Galih-Krasnaya fetishistic relationship in Tabula Rasa. As voyeuristic objects, women bodies are degraded as appropriate territory to be conquered by men; while as a fetishistic object, women are constructed as a